Comprehensive Analysis of Comparison of Trastuzumab Reference with Biosimilars in the Treatment of HER2-Positive Breast Cancer: A Review - Aulia Khaerunisa; Ahsanal Kasasiah; Meisya Dwi Ananda; Naila Yusti Fadhilah; Shofiatulfuadah Retnaningrum Herlaesa (Jurnal Pijar MIPA, 2026)
HER2-positive breast cancer is an aggressive subtype of breast cancer characterized by overexpression of the Human Epidermal Growth Factor Receptor-2 (HER2), which is associated with rapid tumor progression, higher metastasis rates, and poor prognosis. Trastuzumab has become one of the main targeted therapies for HER2-positive breast cancer and has significantly improved patient survival outcomes. However, the high cost of reference trastuzumab products such as Herceptin limits patient access, especially in developing countries. Therefore, trastuzumab biosimilars have emerged as more affordable therapeutic alternatives with comparable clinical performance. This review aimed to analyze and compare the efficacy, pharmacokinetic profile, safety, and cost-effectiveness of reference trastuzumab and trastuzumab biosimilars in the treatment of HER2-positive breast cancer. The method used was a systematic literature review of the PubMed and ScienceDirect databases, using keywords related to breast cancer, trastuzumab, and biosimilars. Studies published between 2014 and 2024 were included based on predetermined inclusion and exclusion criteria. The findings demonstrated that several biosimilars, including SB3 (Ontruzant), CT-P6 (Herzuma), PF-05280014 (Trazimera), ABP 980 (Kanjinti), and trastuzumab-dkst (Ogivri), exhibited equivalent efficacy to reference trastuzumab in terms of pathological complete response (pCR), progression-free survival (PFS), overall survival (OS), and disease-free survival (DFS). In addition, biosimilars showed pharmacokinetic, immunogenicity, and cardiac safety profiles comparable to those of the originator product. Biosimilars also provided significant economic advantages by reducing treatment costs and improving patient access to HER2-targeted therapy. In conclusion, trastuzumab biosimilars are effective, safe, and cost-efficient alternatives to reference trastuzumab for HER2-positive breast cancer management and may support more sustainable healthcare systems.